Blood Cell Parameters Combined with Inflammatory Markers in the Early Diagnosis of Pulmonary Embolism: Blood Cell Parameters and Inflammatory Markers - Li, Dongfu; Yuan, Mengqi; Yang, Huijun (Cellular and Molecular Biology, 2022)
Venous thrombosis is a semi-solid formation of blood components that coalesce in the venous system, and the pathological process of its formation is called venous thrombosis. The deep veins of the lower extremities are a common site of prevalence, and the clinical diagnosis of lower extremity deep vein thrombosis can occur independently or as a complication of other diseases. There is a clear link between inflammation and coagulation/anticoagulation, with inflammatory mechanisms upregulating pro-inflammatory factors, downregulating natural anticoagulant substances, and inhibiting fibrinolytic activity; systemic inflammation is a strong pro-thrombotic stimulus; and in vivo, natural anticoagulant substances not only prevent thrombosis, but also deter inflammatory processes. The interconnection between inflammation and coagulation plays an important role in venous thrombosis. In this study, we analyzed the relationship between inflammatory markers CRP and Fg, FVIII:C and FIX:C by measuring plasma CRP concentration, Fg level, FVIII:C and FIX:C levels in patients with DVT diagnosed by ultrasound, and explored the role and mechanism of inflammatory response and coagulation factor abnormalities and the interaction between them in the development of DVT. In this paper, human blood DNA was extracted by phenol-chloroform-isoamyl alcohol extraction, and CRP 1059G/C gene polymorphism was detected by polymerase chain reaction-restriction enzyme segment length polymorphism (PCR-RFLP) nucleotide typing technique, and the genotypes of each subject were distinguished according to the bands seen by gel electrophoresis, and the frequency of each genotype was counted. Plasma CRP concentrations were measured by immunoturbidimetric assay, FVIII:C and FIX:C levels were measured by phase I assay, and plasma Fg levels were measured by coagulation assay in 59 cases (38 males and 21 females, aged 21-82 years, mean 49.67±11.12 years) and 26 controls (17 males and 9 females, aged 32-67 years, mean 50.13±8.96 years). The above indexes were compared between the two groups, and the correlation between CRP and FVIII:C, FIX:C and Fg was analyzed. Polymerase chain reaction-restriction enzyme segment length polymorphism nucleotide typing technique was used to detect the relationship between CRP 1059G/C gene polymorphism and DVT, to further search for risk factors of venous thrombosis, thus providing new ideas for the future prevention and treatment of this disease in clinical practice.